2014
DOI: 10.1016/j.bbabio.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of oxidative stress and mitochondrial respiratory chain dysfunction in an in vitro model of sepsis-induced kidney injury

Abstract: To investigate the role of oxidative stress and/or mitochondrial impairment in the occurrence of acute kidney injury (AKI) during sepsis, we developed a sepsis-induced in vitro model using proximal tubular epithelial cells exposed to a bacterial endotoxin (lipopolysaccharide, LPS). This investigation has provided key features on the relationship between oxidative stress and mitochondrial respiratory chain activity defects. LPS treatment resulted in an increase in the expression of inducible nitric oxide syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 57 publications
(64 reference statements)
2
90
0
2
Order By: Relevance
“…Mitochondrial oxidant generation in septic AKI plays an important role in renal tubular injury during sepsis, manifested as ischemic injury. 15,16,[35][36][37] Interestingly, mitochondria-targeted antioxidants could attenuate CLP-induced AKI, independent of systemic blood pressure. 17 Our findings showed that TLR9 deficiency helped to prevent renal mitochondrial injury and the subsequent decrease in renal function after CLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial oxidant generation in septic AKI plays an important role in renal tubular injury during sepsis, manifested as ischemic injury. 15,16,[35][36][37] Interestingly, mitochondria-targeted antioxidants could attenuate CLP-induced AKI, independent of systemic blood pressure. 17 Our findings showed that TLR9 deficiency helped to prevent renal mitochondrial injury and the subsequent decrease in renal function after CLP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tubular oxidative stress and mitochondrial dysfunction were proposed as important pathologic changes occurring in septic AKI [15][16][17] ; however, little is known about effects of Tlr9KO on tubular dysfunctions after CLP. 11 Therefore, we evaluated the effects of Tlr9KO on tubular mitochondrial dysfunction after CLP.…”
mentioning
confidence: 99%
“…[23][24][25] A large number of studies have shown that mitochondrial dysfunction plays an important role in the progression of renal disease including renal tubular injury, chronic kidney disease, and acute renal failure, which can lead to renal disease aggravation and progression. [26][27][28] More and more evidences suggested that the damage of mitochondrial morphological and function plays an important role in the development of DN. 29,30 Malik et al 31 found that mitochondrial DNA copy number of peripheral blood in patients with DN is significantly higher than the DM group without nephropathy, which prompted that mitochondrion plays a key role in DN, namely, mitochondrial fission is increasing under HG.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, several different patho-physiological mechanisms have been proposed for sepsis-induced AKI and a growing body of evidence now suggests that inflammatory reactions by systemic cytokine storm or local cytokine production [3], and tubular dysfunction induced by oxidative stress [5] are involved in the mechanisms of this complex and multi-factorial disease.…”
Section: Introductionmentioning
confidence: 99%